Controlled Grafting of Comb Copolymer Brushes on Poly(tetrafluoroethylene) Films by Surface-Initiated Living Radical Polymerizations - Yu, W. H; Kang, E. T; Neoh, K. G (Langmuir, 2005)
Surface modification of poly(tetrafluoroethylene) (PTFE) films by well-defined comb copolymer brushes was carried out. Peroxide initiators were generated directly on the PTFE film surface via radio frequency Ar plasma pretreatment, followed by air exposure. Poly(glycidyl methacrylate) (PGMA) brushes were first prepared by surface-initiated reversible addition-fragmentation chain transfer polymerization from the peroxide initiators on the PTFE surface in the presence of a chain transfer agent. Kinetics study revealed a linear increase in the graft concentration of PGMA with the reaction time, indicating that the chain growth from the surface was consistent with a “controlled” or “living” process. α-Bromoester moieties were attached to the grafted PGMA by reaction of the epoxide groups with 2-bromo-2-methylpropionic acid. The comb copolymer brushes were subsequently prepared via surface-initiated atom transfer radical polymerization of two hydrophilic vinyl monomers, including poly(ethylene glycol) methyl ether methacrylate and sodium salt of 4-styrenesulfonic acid. The chemical composition of the modified PTFE surfaces was characterized by X-ray photoelectron spectroscopy.